(x+y)(x^2-xy+y^2)

(x+y)(x^2-xy+y^2) = x^3 + y^3

Question

Asked 2/24/2014 5:42:04 PM

Updated 2/24/2014 5:57:37 PM

1 Answer/Comment

s

Rating

3

(x+y)(x^2-xy+y^2)

= x^3 + y^3

= x^3 + y^3

Added 2/24/2014 5:57:37 PM

This answer has been confirmed as correct and helpful.

Factor completely, then place the factors in the proper location on the grid.
5c^2 +30c + 45 **Weegy:** Simplifying
5c = 2 + 30c + 45
Reorder the terms:
5c = 2 + 45 + 30c
Combine like terms: 2 + 45 = 47
5c = 47 + 30c
Solving
5c = 47 + 30c
Solving for variable 'c'.
Move all terms containing c to the left, [ all other terms to the right.
Add '-30c' to each side of the equation.
5c + -30c = 47 + 30c + -30c
Combine like terms: 5c + -30c = -25c
-25c = 47 + 30c + -30c
Combine like terms: 30c + -30c = 0
-25c = 47 + 0
-25c = 47
Divide each side by '-25'.
c = -1.88
Simplifying
c = -1.88 ] (More)

Question

Updated 3/20/2014 9:16:12 PM

1 Answer/Comment

(y+1/3)(y-1/3) **Weegy:** (y+1/3)(y-1/3)= y^2 -1/9 **User:** (a + b - c)(a + b + c) **Weegy:** (a + b - c)(a + b + c) = a^2 + 2ab + b^2 - c^2 (More)

Question

Updated 2/24/2014 6:03:06 PM

0 Answers/Comments

31,131,819

questions answered

victoria3

$107.11

Hearts 2,186 Views 8,712 Streams 112

phpmicro

$100.05

Hearts 2,059 Views 257,239 Streams 152

PranaMachine

$80.97

Hearts 1,653 Views 6,405 Streams 87

emdjay23

$72.45

Hearts 1,575 Views 134,622 Streams 114

maydj

$37.45

Hearts 1,252 Views 106,399 Streams 114

jezziem

$33.60

Hearts 865 Views 90,102 Streams 50

wallet.ro

$32.35

Hearts 853 Views 47,579 Streams 43

sacharyn

$30.30

Hearts 668 Views 60,576 Streams 52

There are no comments.